Tight junctions in skin: new perspectives. (November 2012) - Sapra, Bharti; Jindal, Manish; Tiwary, Ashok K
Tight junctions (TJs) are intercellular contacts that seal the space between the individual cells of an epithelial sheet or stratifying epithelia, such as the epidermis, so that they can collectively separate tissue compartments. Intercellular junctions, such as adherens and TJs, play a crucial role in the formation and maintenance of epithelial and endothelial barriers. A variety of components including claudins, occludin, tricellulin, zonula occluden proteins and junctional adhesion molecules have been identified in complex localization patterns in mammalian epidermis. In several skin diseases that are characterized by impaired skin barrier function, altered proliferation/differentiation of the epidermis and/or infiltration of inflammatory cells, altered expression patterns of TJ proteins have been observed. This review is aimed at providing an insight into the molecular composition, tools for identification and understanding the role of TJs in skin diseases and barrier function regulation.